2015
DOI: 10.1021/acsami.5b00311
|View full text |Cite
|
Sign up to set email alerts
|

Probing Molecular Packing at Engineered Interfaces in Organic Field Effect Transistor and Its Correlation with Charge Carrier Mobility

Abstract: Surface engineering of SiO2 dielectric using different self-assembled monolayer (SAM) has been carried out, and its effect on the molecular packing and growth behavior of copper phthalocyanine (CuPc) has been studied. A correlation between the growth behavior and performance of organic field effect transistors is examined. Depth profiling using positron annihilation and X-ray reflectivity techniques has been employed to characterize the interface between CuPc and the modified and/or unmodified dielectric. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…6ii). 45,48,49 As discussed, the surface energy of the substrate will greatly inuence the initial nucleation behaviour of the deposited material and determine the nal growth mode. 17,20,45,48 By using SAMs to selectively tune surface energy, island, layer-by-layer, and SK growth can be achieved using the same deposited material and fabrication conditions.…”
Section: Nucleation Densitymentioning
confidence: 99%
“…6ii). 45,48,49 As discussed, the surface energy of the substrate will greatly inuence the initial nucleation behaviour of the deposited material and determine the nal growth mode. 17,20,45,48 By using SAMs to selectively tune surface energy, island, layer-by-layer, and SK growth can be achieved using the same deposited material and fabrication conditions.…”
Section: Nucleation Densitymentioning
confidence: 99%
“…Height profile of RT deposited CuPc film (Figure 1a) shows 2D + island growth mode with some of the grains having heights much less than 1.3 nm, which is the length of CuPc molecule. 23 The average surface roughness of the film was about 0.5 nm. If the molecule had been standing upright, one monolayer height would have been close to 1.3 nm, but because of significant tilting, the height is much less than 1.3 nm.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous study, we have discussed the necessity of techniques that can be used to study the buried interfaces and have demonstrated the potentiality of positron annihilation technique, complemented with X-ray reflectivity (XRR), to identify the growth conditions at buried interfaces. 23 Though Atomic Force Microscopy (AFM) is commonly used to study initial growth conditions, changes in interface conditions with increase in thickness of active layer at which the device operates, necessitates employment of techniques like positron annihilation, XRR, etc., to probe buried interfaces. Reflectivity measurements in specular mode of X-ray reflectivity technique map the variations in electron density along the direction normal to the surface providing useful information about the thickness of the layers and surface/interface properties with high sensitivity and nanometer accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…This difference can be attributed to the differing initial growth conditions. As mentioned before, one of our previous studies has clearly shown that on unmodified SiO 2 CuPc films exhibit 2D þ island growth mode while on OTS modified SiO 2 they grow in more 3D fashion, with clear voids between the grains [21]. Presence of large voids could be requiring higher thickness of CuPc film to improve connectivity between the grains thereby resulting in attainment of maximum mobility at an increased thickness compared to that on unmodified SiO 2 .…”
Section: Currentevoltage Characteristicsmentioning
confidence: 60%
“…It should be pointed out that even in that study, focus has been made on only mobility and there is no discussion on hysteresis and threshold voltage stability. Our earlier studies have shown change in the growth mode of copper phthalocyanine (CuPc) films on octadecyltrichloailane (OTS) modified SiO 2 (with surface energy much lower than that of CuPc) as compared to that on unmodified SiO 2 and increase in hysteresis for 30 nm thick CuPc film based OFETs on the former than that on the latter [21,22]. Therefore, in the present study, we have tried to determine the optimum thickness on such hydrophobic surfaces to obtain minimum hysteresis and higher mobility.…”
Section: Introductionmentioning
confidence: 99%